896. Cost-Avoidance Associated with Active Stewardship of Remdesivir. (15th December 2022) - Dyer, April; Locklear, Eric; Okoye, Obiefuna; Ashley, Elizabeth Dodds
Abstract: Background: The COVID pandemic shifted antimicrobial stewardship resources at community hospitals. One reason for this shift was new COVID treatments, the first of which was remdesivir, which received initial emergency use authorization (EUA) for the treatment of COVID-19 in May 2020. The UNC Health Southeastern (UNC SEH) pharmacy director stewarded remdesivir by reviewing patients to ensure they met emergency use authorization (EUA) and guideline-based appropriateness criteria. The infectious diseases physician resolved any disputes regarding patient candidacy for remdesivir. The goal of remdesivir stewardship was to optimize care; however, the shift in workflow presented an unrecognized opportunity for stewards to reduce remdesivir costs. Methods: The percentage of COVID patient admissions receiving remdesivir at UNC SEH for calendar years 2020 and 2021 was benchmarked against 32 community hospitals in the Duke Antimicrobial Stewardship Outreach Network (DASON) (Figure 1). UNC SEH purchasing data were used to calculate remdesivir expenditures for 2020 and 2021. Next, the anticipated cost if the hospital had prescribed remdesivir to the same percentage of admissions as the DASON mean was calculated. The difference was calculated to determine the cost avoidance achieved by having below average use of remdesivir (Table 1). Results: At UNC SEH, 28.1% of COVID admissions received remdesivir in 2020 and annual remdesivir expenditures were $693, 680. In 2021, 47.45% of COVID-19 admissions received remdesivir and drug expenditures were $1, 248, 000. The DASON mean % of COVID admissions receiving remdesivir in 2020 was 44.08% and 60.07% in 2021. A total cost avoidance of $726, 407 was calculated based on the hospital's below-benchmark use of remdesivir (Table 1). Conclusion: UNC SEH achieved significant cost-savings in 2020 and 2021 due to active remdesivir stewardship. The team created a patient-centered model that focused on using drugs for the right patients and the organization realized cost-savings while ensuring that patients received therapy in accordance with remdesivir EUAs and published guidelines. Disclosures: All Authors : No reported disclosures.